Technological affordance discovery in enterprise social media success. Issue 10 (22nd July 2020) - Ng, Keng Hong; Yee, Rachel W.Y.
Abstract : Purpose: This paper aims to build on affordance theory from a discovery perspective, to illustrate how motivations and goals behind enterprise social media adoption by companies in the fashion and apparel industries are discovered and realized in performance. Enterprise social media and its exogenous technological affordances are introduced as action opportunities in an organization during implementation, to be discovered and acted upon by users to effect various performance outcomes. Design/methodology/approach: A case study approach was adopted. Data was collected on five fashion companies that have implemented enterprise social media for their internal communication. Findings: The findings show that fashion companies adopt enterprise social media offered by external vendors to actively seek more effective internal communication and collaboration among their employees. However, fashion companies embark on different pathways of discovering and actualizing the affordances from the newly implemented enterprise social media. As a result, these firms achieved various kinds of performance benefits, which range from improved customer loyalty to enhanced innovation performance. Originality/value: This study is the first to introduce a discovery perspective to affordance theory and systematically document the success of enterprise social media appropriation by companies in the fashion and apparel industries.